Malic Acid Distribution and Degradation in Grape Must During Skin Contact: The Influence of Recombinant Malo-Ethanolic Wine Yeast Strains - van Staden, J.; Volschenk, H.; Van Vuuren, H.J.J.; Viljoen-Bloom, M. (South African Journal of Enology and Viticulture, 2017)
Wine acidity plays an important role in determining wine quality and ensuring physiochemical and microbiological stability. In high-acid wines, the L-malic acid concentration is usually reduced through bacterial malolactic fermentation, while acidulation in low-acidity wines is usually done during final blending of the wine before bottling. This study showed that skin contact did not influence the relative concentration of L-malic acid in the pulp and juice fractions from Colombard, Ruby Cabernet and Cabernet Sauvignon grape musts, with 32%-44% of the L-malic acid present in the pulp fraction. Four recombinant malo-ethanolic (ME) Saccharomyces wine yeast strains containing the malic enzyme (mae2) and malate transporter (mael) genes of Schizasaccharomyces pombe, effectively degraded the L-malic acid in both the juice and pulp fractions of all three cultivars, with a complete degradation of malic acid in the juice fraction within 2 days.